(untitled) (Web of Teachers: Inderscience Research, 2024)
The article shows the issue of acquiring knowledge and acquiring knowledge in the works of Eastern scholars. Also, it is determined that the rational and effective organization of the educational process with students is the basis of their acquisition of knowledge. Especially in the views of Eastern thinkers, it is noted that individual talent and talent are connected with their desire to know.